A modified Allam cycle without compressors realizing efficient power generation with peak load shifting and CO2 capture. (1st May 2019) - Zhu, Zilong; Chen, Yaping; Wu, Jiafeng; Zhang, Shaobo; Zheng, Shuxing
Abstract: A modified Allam cycle (Allam-Z cycle) with a simpler system was proposed and investigated using NG (natural gas)/O2 combustion products mixing with the circulation CO2 as the working medium for power generation with high efficiency, zero CO2 emission and peak load shifting. The modifications are that all the working media are pumped to high pressure by pumps instead of compressors, the cold energy of both liquid oxygen and LNG is used for degrading the cooling water for CO2 liquefaction and a set of regenerative heat exchangers are arranged for turbine exhaust heat recovery. The influences of turbine parameters on the performances of the cycle were investigated. The comparison was performed under the conditions of condensation temperature of 30 °C, turbine inlet pressure of 30 MPa, inlet temperature of either 700 °C or 900 °C and the turbine outlet pressures of Allam-Z cycle and Allam cycle are 7.21 MPa and 4 MPa respectively. The results show that the output power efficiency and the equivalent net efficiency of the Allam-Z cycle with full CO2 capture are 43.64% and 40.83% respectively or 50.87% and 48.05% respectively, which are 2.15% or 2.96% higher than those of the Allam cycle under the same condition. Highlights: A modified Allam cycle was studied with combustion product and CO2 as working medium. Cycle system is simplified with higher turbine back pressure to eliminate compressor. The cycle integrates power generation with CO2 capture and energy shifting. Equivalent net efficiency is adopted considering 1/4 ASU consumed off-peak power. Equivalent net efficiency is 48.05% with turbine inlet parameters of 30 MPa/900 °C.